Comparison Of Love And Secret Poetry Love Letter Of Poetry For The Silent Princess By Ahmadun Yosi Herfanda - Muhammad Miftah Sabban (Al-Makki Publisher, 2023)
This study describes the similarities and differences in the poetry of Secret Love and a Love Letter for Miss Silent by Ahmadun Yosi Herfanda. The purpose of this research is to compare the poetry of Secret Love and Love Letters for Miss Silent by Ahmadun Yosi Herfanda. This study uses a content analysis method whose data sources are obtained from the poems Secret of Love and Love Letters for Puan Sunyi using a comparative literature approach that focuses on the theory put forward by Remak. The results of this study indicate that the theme in the secret love poem is a description of the wealth of love which not everyone can interpret according to the rules of true love. The message that the author wants to convey through the secret love poem is the true essence of love. Meanwhile, the love letter Poetry for Silent Puan has the theme of missing someone who was once present in her life. The message that the author wants to convey in the love letter poem to Miss Silent is that longing makes people anxious. The similarities between the secret love poem and the love letter to Miss Silent by Ahmadun Yosi Herfanda are that both of these poems are of a new type, included in the ranks of poetry of romance and elegy (sadness). In addition, both of these poems are poetry expressions of protest by a poet explaining his true feelings, with expressions of advice and sadness. The difference between secret love poems and love letters for silent ladies lies in their meaning and message.